2020
DOI: 10.1186/s40364-019-0180-0
|View full text |Cite
|
Sign up to set email alerts
|

LOX family and ZFPM2 as novel diagnostic biomarkers for malignant pleural mesothelioma

Abstract: Background: Malignant pleural mesothelioma (MPM) is a rare and aggressive cancer that develops in the pleural and outer layer of tissues surrounding the lungs. MPM is primarily caused by occupational exposure to asbestos and results in a poor prognosis. Effective therapeutics as well as early diagnostics for the MPM are still lacking. To identify potential diagnostic biomarkers for MPM, we performed bioinformatics analysis of public database. Methods: Utilizing databases from Cancer Cell Line Encyclopedia (CCL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 41 publications
7
34
0
Order By: Relevance
“…For example, targeted deletion of PD-1 in myeloid cells was already shown to induce antitumor immunity [ 52 ]. Similar to our results, therapeutic modulation of myeloid polarization through the IFN-γR/STAT1 signaling axis was found to enhance antitumor immune function by activating tumor infiltrating myeloid cells, regulating PD-L1 expression, and promoting immunogenic cell death [ 53 , 54 , 55 , 56 , 57 , 58 ]. New studies indicate that autophagy in addition to its cell-autonomous antitumorigenic functions inhibits cancer development by orchestrating inflammation and immunity.…”
Section: Discussionsupporting
confidence: 89%
“…For example, targeted deletion of PD-1 in myeloid cells was already shown to induce antitumor immunity [ 52 ]. Similar to our results, therapeutic modulation of myeloid polarization through the IFN-γR/STAT1 signaling axis was found to enhance antitumor immune function by activating tumor infiltrating myeloid cells, regulating PD-L1 expression, and promoting immunogenic cell death [ 53 , 54 , 55 , 56 , 57 , 58 ]. New studies indicate that autophagy in addition to its cell-autonomous antitumorigenic functions inhibits cancer development by orchestrating inflammation and immunity.…”
Section: Discussionsupporting
confidence: 89%
“…Studies have shown that LOX mRNA level was increased in various cancer types, including head and neck squamous cell carcinoma, and breast and prostate cancers (Kirschmann et al, 2002;Lapointe et al, 2004;Erler et al, 2006). Recently, LOX was identified as a potential diagnostic biomarker in MPM (Kim et al, 2020). We also note that patients with high expression of LOX had shorter overall survival time and worse prognosis compared with patients with low expression of LOX (Supplementary Figures 4E, 5E).…”
Section: Discussionsupporting
confidence: 58%
“…At last, the four genes, DTNA, PRR11, TMEM178B, and CACNA1D, were mainly related to gastric cancer or prostate cancer [ 39 42 ]. In miRNA-targeted genes of READ, ZFPM2 was recommended as a diagnostic biomarker for malignant pleural mesothelioma and PLXNA1 and PTPRU were related to lung cancer or colon cancer [ 43 46 ]. Combining the expression levels of those target genes with TNM stage classification, SERPINE1 is the most important gene associated with tumor size and metastasis status in COAD.…”
Section: Discussionmentioning
confidence: 99%